2022
DOI: 10.3390/ani12151956
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Applications of Cattle Mesenchymal Stromal Cells

Abstract: Attention on mesenchymal stromal cells (MSCs) research has increased in the last decade mainly due to the promising results about their plasticity, self-renewal, differentiation potential, immune modulatory and anti-inflammatory properties that have made stem cell therapy more clinically attractive. Furthermore, MSCs can be easily isolated and expanded to be used for autologous or allogenic therapy following the administration of either freshly isolated or previously cryopreserved cells. The scientific literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…The isolation, in vitro differentiation and immunophenotype of bovine MSCs has already been reported (Table 1). As shown in Table 1, it is clear that bovine MSCs represent a heterogeneous cell population with differences originating from donor age, tissue of origin, genetic background, passage, and culture conditions [10, 51, 52]. For example, Kato et al showed that bone marrow (BM)‐derived bovine MSCs lacked CD90 expression, while other researchers showed a variable expression of CD90 (Table 1) [53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation, in vitro differentiation and immunophenotype of bovine MSCs has already been reported (Table 1). As shown in Table 1, it is clear that bovine MSCs represent a heterogeneous cell population with differences originating from donor age, tissue of origin, genetic background, passage, and culture conditions [10, 51, 52]. For example, Kato et al showed that bone marrow (BM)‐derived bovine MSCs lacked CD90 expression, while other researchers showed a variable expression of CD90 (Table 1) [53].…”
Section: Introductionmentioning
confidence: 99%
“…The isolation, in vitro differentiation and immunophenotype of bovine MSCs has already been reported (Table 1). As shown in Table 1, it is clear that bovine MSCs represent a heterogeneous cell population with differences originating from donor age, tissue of origin, genetic background, passage, and culture conditions [10,51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Bovine MSCs isolated from different adult and fetal tissues have been shown to be immunophenotypically positive for CD29, CD44, CD73, CD90, CD105, CD166, CD49d, CD13 and MHC-I antigens and negative for CD45, CD34, CD14, CD31, CD117, CD74, CD11b, CD80, CD86, CD106 and MHC-II surface markers (Merlo et al, 2022;Wang et al, 2022, Cahuascanco et al, 2019.…”
Section: Immunophenotypic Cytobiochemical Cytophysiological and Molec...mentioning
confidence: 99%
“…Nowadays, in veterinary medicine, the owners require their animals to be treated with sophisticated and new treatments with the aim to improve the patient’s life quality but also, in the case of livestock animals, to improve the quality of products, aiming to preserve human health [ 1 ]. MSCs therapy could be then considered as an opportunity for researchers, veterinary practitioners, and animal owners for contributing to animal and human health and well-being.…”
mentioning
confidence: 99%